RETROSPECTIVE STUDY ON THE FREQUENCY OF ORO-MAXILLOFACIAL TRAUMAS AT ”SF. SPIRIDON” HOSPITAL IN IAȘI(2021-2022) - Giuvara Constantin Răzvan; Botnariu Eosefina Gina; Cernei Eduard Radu; Victor Vlad Costan; Diana Bulgaru Iliescu (Romanian Journal of Oral Rehabilitation, 2024)
Maxillofacial injuries are a major preventable and epidemic public health problem worldwide; they are increasing significantly in the population, affecting both physically and mentally millions of people, and overburdening health systems. The aim of the study is to assess the forensic aspects (cause, mode of occurrence and outcome) in relation to demographic parameters (age, gender, residence). Material and methods: 153 cases were selected between January 2021 and December 2022 from the database of the Emergency and Oral and Maxillofacial Surgery departments of the “Sf. Spiridon” Hospital in Iasi. Data collected included demographics, mechanism of trauma, mode of injury, treatment and evolution. Comparisons of the collected data were made based on age, gender, and residence. Results: Male subjects presenting a higher number of traumatic injuries and of greater severity compared to female subjects. Cause of traumas: assault (61.4%), vehicle accidents (24.8%) falls from height (3.3%) or injuries caused by animals (4.6%). 61.4% of traumas were mandibular fractures, followed by maxillary fractures (27.5%), nasal pyramid fractures (2.7%), and the fewest were frontal bone fractures (0.7%). Dental avulsion (17.6%) , soft tissue contusions (10.5%), dental dislocations and hematomas (3.3%) were injuries associated with the main lesion. 75.2% of injuries benefited from surgical treatment, while 24.8% were treated conservatively. 95.4% of cases, the evolution was favorable. Conclusions: Maxillofacial trauma frequently presents in emergency departments as a common injury. Globally, maxillofacial injuries constitute a major public health concern. Affecting millions both physically and mentally, these injuries significantly burden healthcare systems around the world.